PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS XI DI SMA NEGERI 5 PARIAMAN - Elvira, Desri (Departemen Matematika, 2024)
The background to this research is that student learning outcomes in mathematics subjects are still low. The aim of this research is to determine and describe the effect of implementing the Discovery Learning model on the learning outcomes of class XI students at SMA Negeri 5 Pariaman. This type of research uses quasy experiments (experimental power). The research sample consisted of 52 people. Data analysis techniques consist of normality tests, homogeneity tests and hypothesis tests. The results of the research show that the final test learning outcomes of experimental class students are higher than the final test learning outcomes of the control class. There are differences in the mathematics learning outcomes of students taught using the discovery learning model compared to the direct learning model in Mathematics for class XI students at SMA 5 Pariaman p-value >0.05 means H1 is accepted and H0 is rejected.Keywords– Discovery Learning Learning Model, Learning Outcomes